Budget Classification - Bouley, Dominique (Technical Notes and Manuals; Technical Notes and Manuals ;, 2009)
This technical note analyzes the importance of a budget classification system. It highlights that budget classification is one of the fundamental building blocks of a sound budget management system, as it determines the manner in which the budget is recorded, presented and reported, and as such has a direct impact on the transparency and coherence of the budget. The note describes the main features of a sound budget classification system, structuring of a budget classification system, and the relationship between budget classification and the chart of accounts.